Snapshot of the pharmaceutical promotional literature of Bangladesh: A critical review (Bangladesh Journal of Pharmacology, 2018)
The present research was conducted to evaluate the quality of pharmaceutical promotional literature. Indications was mentioned in 88.2% promotional literature and less than half (40.0, 33.9 and 38.9%) of these contains side effects, precautions and contraindications respectively. Among the provided information 67.3%, 16.5%, 19.5% and 24.0% matched with the BDNF/BNF respectively. Scientific articles (73.3%) were cited most followed by commercial online sources (15.5%), data on file (4.2%), regulatory body approval data (2.9%), product monograph (2.7%) and textbook/reference book (1.6%). Only half (50.2%) of these cited references were retrievable and no ‘data on file’ could be retrieved. Though most (73.2%) of the promotional claims were true, 13.7, 5.9, 4.6 and 2.6% were identified as false, exaggerated, ambiguous and controversial respectively. This revelation about the quality of promotional literature might an eye opener for the policy makers. More importantly, this may bring alertness among the physicians during interpretation of pharmaceutical promotion literature.